2000
DOI: 10.1038/sj.ijo.0801242
|View full text |Cite
|
Sign up to set email alerts
|

The perceived relative worth of reaching and maintaining goal weight

Abstract: Excessive value may be placed on attaining less than realistic weight goals, particularly but not exclusively by treatment-seeking and heavier obese people and those who desire greater weight loss. Clinicians should take this phenomenon into consideration, and public health initiatives should attempt to place body weight in a more balanced perspective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
23
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 20 publications
2
23
0
Order By: Relevance
“…48 In the present study, prospective weight outcome evaluations reported at baseline were significantly more stringent in eventual noncompleters than in completers, suggesting that more realistic expectations towards weight loss are an important, independent cognitive indicator of readiness to complete treatment. It has been frequently argued that false hope and the desire to lose more weight than what realistically can be expected may Predictors of success in weight loss PJ Teixeira et al increase the likelihood of early disappointment and relapse upon smaller than wanted changes.…”
Section: Discussionmentioning
confidence: 47%
“…48 In the present study, prospective weight outcome evaluations reported at baseline were significantly more stringent in eventual noncompleters than in completers, suggesting that more realistic expectations towards weight loss are an important, independent cognitive indicator of readiness to complete treatment. It has been frequently argued that false hope and the desire to lose more weight than what realistically can be expected may Predictors of success in weight loss PJ Teixeira et al increase the likelihood of early disappointment and relapse upon smaller than wanted changes.…”
Section: Discussionmentioning
confidence: 47%
“…Despite initial weight-loss recommendations of 5-10 % (15,16) , research suggests that adults expect to lose 21-28 % of their starting weight within the first year of treatment (17)(18)(19)(20) , with desired weight losses as high as 34 % (18,20) . Most of these studies examined weight-loss expectations among middle-aged cohorts (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28) or the general population (17,(29)(30)(31)(32)(33)(34) . A small (n 44) Italian study of 18-35-year-old women reported that non-obese women would need to lose 18 % and obese women 23 % of their current weight to reach their ideal weight (35) .…”
mentioning
confidence: 99%
“…Women (mean age of 38·2 years) who enrolled in a weight management intervention were more likely to report appearance rather than improving health as the key motivation for enrolment, when compared with males (17) . Findings from the US National Weight Control Registry suggest that young adults (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) years) who maintained a weight loss for at least 1 year were more likely to report improved appearance or social factors as their primary motivators for weight loss and less likely to report health concerns as their motivation, when compared with older adults (36-50 years) (39) . These findings suggest that young women have different motivations for wanting to control their weight; however, these studies were restricted to individuals already enrolled in a weight-loss intervention or who had achieved successful weight-loss maintenance and therefore may not be representative of young women generally.…”
mentioning
confidence: 99%
“…This outcome could be explained by an aversion to goals perceived as impossible, or unsatisfying [23]. Several studies show that participants with obesity are not motivated by an overall weight-loss goal of 5-10%, as is recommended by health professionals, but rather a weight-loss goal of 22-34% [24][25][26]. This failure to meet the expectations of patients with obesity suggests that there needs to be a smaller disparity between actual and expected outcomes.…”
Section: Primary Improvementsmentioning
confidence: 99%